Improving combination cancer therapy: the CombiPlex® development platform. (June 2018) - Tolcher, Anthony W; Mayer, Lawrence D
Current combination therapy approaches assume that better outcomes are achieved by combining drugs at their maximally tolerated doses. However, administration of individual agents cannot consistently deliver synergistic drug ratios to tumor cells due to differences in pharmacokinetics of the individual drugs. Further, the toxicity of combination regimens often necessitates administration of suboptimal dosages. Delivery technologies, such as the CombiPlex ® platform, can enable efficient and sustained delivery of combination treatments at a synergistic ratio. The CombiPlex platform determines synergistic drug ratios in vitro and identifies an appropriate nanoscale carrier to maintain that ratio in vivo and enhance its delivery to tumor cells. CPX-351, a dual-drug liposomal encapsulation of cytarabine and daunorubicin, is the first clinical proof-of-concept example of the CombiPlex platform. Graphical abstract: